Rencana Pelaksanaan Pembelajaran Kurikulum 2013 Pendidikan Anak Usia Dini di Taman Kanak-Kanak se-Ciputat - Hayati, Miratul; Lestari, Masroro Diah Wahyu; Rahayuni, Chikita (Association of Indonesian Islamic Kindergarten Teachers Education Study Program, 2019)
Curriculum 2013 (K.13) PAUD is developed systematically to fullfil the development needs of children through the development of potential, character and knowledge. This can be seen in the Standards for the Level of Achievement of Children (STPPA), Ministerial Regulation (Permen) 146 of 2014, and Guidelines for Early Childhood Character Education. The policy contained in K.13 PAUD also has the most important position in regulating all activities in the school. This study aims to examine the complete structure of the contents of the Daily Learning Implementation Plan (RPPH) made by educators which will be assessed through the Teacher Skills Assessment Tool (APKG) format based on the 2013 Early Childhood Education Curriculum (K.13 PAUD), which is carried out on 15 Kindergarten group A and group B in the Ciputat region. The results obtained from this study present the lowest percentage seen in the ability of educators to formulate and compile indicators of core competencies, learning objectives, and to plan scientific activities. This shows that there are still many schools that have not followed the procedures for making RPPH based on the implementation guidelines of  K.13 PAUD.